New records for Ameiva ameiva (L., 1758) (Squamata, Teiidae) in Argentina - Cabrera, Mario Roberto (2002)
Several new specimens revised by the author confirm and extend the known range of this macroteiid lizard in Tucumán, Santiago del Estero, and Entre Ríos provinces (Argentina). The presence of the species at La Quiaca (Jujuy province) is commented and determined as being questionable.